Numerical Simulation of the Effect of Cloud Condensation Nuclei Concentration on the Microphysical Processes in Typhoon Usagi - Xiying Ye; Qimin Cao; Baolin Jiang; Wenshi Lin (Advances in Meteorology)
The Weather Research and Forecasting model version 3.2.1 with the Lin microphysics scheme was used herein to simulate super typhoon Usagi, which occurred in 2013. To investigate the effect of the concentration of cloud condensation nuclei (CCN) on the development of typhoon Usagi, a control simulation was performed with a CCN concentration of 100 cm−3, together with two sensitivity tests: C10 and C1000, having CCN concentrations of 10 cm−3 and 1000 cm−3, respectively. The path, intensity, precipitation, microphysical processes, and the release of latent heat resulting from the typhoon in all three simulations were analyzed to show that an increase in CCN concentration leads to decreases in intensity and precipitation, an increase of the cloudless area in the eye of the typhoon, a more disordered cloud system, and less latent heat released through microphysical processes, especially the automatic conversion of cloud water into rainwater. Overall, an increase in CCN concentration reduces the total latent heat released during the typhoon suggesting that typhoon modification by aerosol injection may be optimized using numerical simulations to ensure the strongest release of latent heat within the typhoon.